If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(k + k + k + k) + 3 = 12 + -1k Combine like terms: k + k = 2k 2(2k + k + k) + 3 = 12 + -1k Combine like terms: 2k + k = 3k 2(3k + k) + 3 = 12 + -1k Combine like terms: 3k + k = 4k 2(4k) + 3 = 12 + -1k Remove parenthesis around (4k) 2 * 4k + 3 = 12 + -1k Multiply 2 * 4 8k + 3 = 12 + -1k Reorder the terms: 3 + 8k = 12 + -1k Solving 3 + 8k = 12 + -1k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add 'k' to each side of the equation. 3 + 8k + k = 12 + -1k + k Combine like terms: 8k + k = 9k 3 + 9k = 12 + -1k + k Combine like terms: -1k + k = 0 3 + 9k = 12 + 0 3 + 9k = 12 Add '-3' to each side of the equation. 3 + -3 + 9k = 12 + -3 Combine like terms: 3 + -3 = 0 0 + 9k = 12 + -3 9k = 12 + -3 Combine like terms: 12 + -3 = 9 9k = 9 Divide each side by '9'. k = 1 Simplifying k = 1
| X(x+6)=400 | | 5x-3x-8=4 | | 3x+x-15=37 | | 6(8-y)=36 | | 7n-10=6+n(5-2) | | x+0.05x=800 | | -8a+(a+7)=1 | | -4x+2x-10=10 | | 4(5y-2)=25 | | -4-5x+3x=12 | | -5x-16-2x=26 | | -6-5x+4x=6 | | 3x+30=x+14 | | -12+2x+x=24 | | -14+14v=-10 | | 2(x^2+3x+10)=0 | | (13a^2-6a^5-2a)-(10a^2-11a^5+9a)= | | x+3x-27=25 | | -2x+4x-3=9 | | -3y+9=-2(3y+6) | | -4x+2x-17=9 | | 10x+29=4x+173 | | x-41-6x=29 | | 5a+(8+a)= | | 6*6*6*6*6= | | x^2+x-1=9 | | 6x-4x-9=15 | | 3x+10-x=9+4x-5 | | 15a+4b=66 | | 21z^2+85z-28=0 | | 8*7*6*5*4*3*2= | | 2g^2-g-6=0 |